2013
DOI: 10.1155/2013/109841
|View full text |Cite
|
Sign up to set email alerts
|

Does Playground Improvement Increase Physical Activity among Children? A Quasi-Experimental Study of a Natural Experiment

Abstract: Outdoor recreational spaces have the potential to increase physical activity. This study used a quasi-experimental evaluation design to determine how a playground renovation impacts usage and physical activity of children and whether the visitations correlate with children's physical activity levels and parental impressions of the playground. Observational data and intercept interviews were collected simultaneously on park use and park-based activity among playground visitors at pre- and postrenovation at an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 43 publications
1
60
1
2
Order By: Relevance
“…The number of natural experiments that aim to evaluate changes to the built environment on PA behaviours among children is increasing but they are still scarce (Bohn-Goldbaum et al, 2013;Quigg et al, 2012;Smith et al, 2012). The innovation in the WCMC study is the possibility to objectively evaluate total daily context-specific behaviour as it is otherwise not possible to rule out substitution as expressed in the Activitystat hypothesis (Gomersall et al, 2013).…”
Section: Weekdaysmentioning
confidence: 99%
“…The number of natural experiments that aim to evaluate changes to the built environment on PA behaviours among children is increasing but they are still scarce (Bohn-Goldbaum et al, 2013;Quigg et al, 2012;Smith et al, 2012). The innovation in the WCMC study is the possibility to objectively evaluate total daily context-specific behaviour as it is otherwise not possible to rule out substitution as expressed in the Activitystat hypothesis (Gomersall et al, 2013).…”
Section: Weekdaysmentioning
confidence: 99%
“…In an Australian-based study, the number of children and teen park users increased between baseline and six-months post-intervention, although p-values were not provided (Veitch et al, 2012). In another Australian-based study, no detectable difference between the mean number of children using the parks was observed at the two year follow-up time point (p ¼0.42) (Bohn-Goldbaum et al, 2013). Three studies undertaken in the USA showed a decline in the number of children and adolescent park users post-intervention (p-values not provided) (Cohen et al, 2009(Cohen et al, , 2012Tester and Baker, 2009).…”
Section: Parks and Playgroundsmentioning
confidence: 95%
“…More specifically, individual domains measuring confounding (Bohn-Goldbaum et al, 2013;Cohen et al, 2009Cohen et al, , 2012Roemmich et al, 2014;Tester and Baker, 2009;Veitch et al, 2012), selection of participants (Bohn-Goldbaum et al, 2013;Cohen et al, 2009Cohen et al, , 2012Davidson et al, 1994;Quigg et al, 2012;Tester and Baker, 2009;Veitch et al, 2012), missing data (Bohn-Goldbaum et al, 2013;Cohen et al, 2009Cohen et al, , 2012Roemmich et al, 2014;Tester and Baker, 2009;Veitch et al, 2012) and measurement outcomes (Bohn-Goldbaum et al, 2013;Cohen et al, 2009Cohen et al, , 2012Roemmich et al, 2014;Tester and Baker, 2009;Veitch et al, 2012) were frequently assessed as at a serious risk of bias. The sampling strategy for study sites was non-randomised for seven studies (Bohn-Goldbaum et al, 2013;Cohen et al, 2009Cohen et al, , 2012Davidson et al, 1994;Quigg et al, 2012;Tester and Baker, 2009;Veitch et al, 2012), of which six incorporated comparison sites within the study design (Bohn-Goldbaum et al, 2013;Cohen et al, 2009;Davidson et al, 1994;Quigg et al, 2012;Tester and Baker, 2009;…”
Section: Parks and Playgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children are perceptive and could be positively or negatively influenced by their parents' dietary and activity behaviors. In addition, parents have the opportunity to promote outside activities by actively engaging, providing encouragement, or being present in and during neighborhood recreational activities (i.e., playground) [56].…”
Section: Implications For Practicementioning
confidence: 99%